Investigation Of Automotive Air Conditioning Using Eco-Friendly R600a As An Alternative Refrigerant To R134a - Sumeru, Kasni; Arman, Muhammad; Wellid, Ismail; Simbolon, Luga Martin; Setyawan, Andriyanto; bin Sukri, Mohamad Firdaus (Jurnal Polimesin, 2024)
One of the main reasons for replacing R134a with R600a is the impact of global warming. In this study, a numerical approach was applied to investigate changes in automotive air conditioning (AAC) performance due to the replacement of R134a with R600a. A thermodynamic evaluation was carried out with evaporating and condensing temperatures of 5oC and 45oC, respectively. The study simulates AAC performance at five engine rotation speeds: 1000, 2000, 3000, 4000 and 5000 rpms. The results show that replacing R134a with R600a reduces the cooling capacity and input power by 45.42% and 47.02%, respectively. However, due to the dominant decrease in input power as compared to the decrease in cooling capacity, the COP of AAC increases by 2.93%. Although the increment in COP is relatively small, this replacement greatly contributes to the reduction of greenhouse gas emissions that causes the problem of global warming due to the lower GWP of R600a as compared to R134a.